2014
DOI: 10.1177/0956797614531602
|View full text |Cite
|
Sign up to set email alerts
|

Forgiving You Is Hard, but Forgetting Seems Easy

Abstract: Forgiveness is considered to play a key role in the maintenance of social relationships, the avoidance of unnecessary conflict, and the ability to move forward with one’s life. But why is it that some people find it easier to forgive and forget than others? In the current study, we explored the supposed relationship between forgiveness and forgetting. In an initial session, 30 participants imagined that they were the victim in a series of hypothetical incidents and indicated whether or not they would forgive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
5
26
1
Order By: Relevance
“…Interestingly, our study did not show increased suppression-induced forgetting between the two and eight repetition conditions. Although this is inconsistent with some previous findings (Anderson & Green, 2001;Anderson et al, 2004;Noreen & MacLeod, 2013Noreen, Bierman & MacLeod, 2014), it should be noted that other studies have also reported no significant increase in the size of the suppression-induced forgetting effect with increased repetitions (Hertel & Calcaterra, 2005). One reason for this discrepancy may relate to the fact that different studies have used a different number of repetitions.…”
Section: Discussioncontrasting
confidence: 95%
“…Interestingly, our study did not show increased suppression-induced forgetting between the two and eight repetition conditions. Although this is inconsistent with some previous findings (Anderson & Green, 2001;Anderson et al, 2004;Noreen & MacLeod, 2013Noreen, Bierman & MacLeod, 2014), it should be noted that other studies have also reported no significant increase in the size of the suppression-induced forgetting effect with increased repetitions (Hertel & Calcaterra, 2005). One reason for this discrepancy may relate to the fact that different studies have used a different number of repetitions.…”
Section: Discussioncontrasting
confidence: 95%
“…However, as previous studies (e.g. Noreen and MacLeod, 2013;Noreen, Bierman and MacLeod, 2014) have demonstrated significant belowbaseline forgetting using a similar number of trials we did not expect this to affect our results.…”
Section: Participantssupporting
confidence: 47%
“…Recent psychological research has sought to establish the extent to which we possess executive control over which memories come to mind, and the mechanisms responsible. Using a wide range of materials, it is now well-established that the repeated attempt to consciously forget unwanted memories impairs their subsequent recall, although debate continues about the nature of the underlying mechanism responsible for such forgetting ( Anderson and Green, 2001 ; Anderson et al, 2004 , 2011 ; Bergström et al, 2009 ; Hanslmayr et al, 2010 ; Noreen and MacLeod, 2013 , 2014, 2015 ; Noreen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%